Apolipoprotein C-III reduction in subjects with moderate hypertriglyceridaemia and at high cardiovascular risk - Tardif, Jean-Claude; Karwatowska-Prokopczuk, Ewa; Amour, Eric St; Ballantyne, Christie M; Shapiro, Michael D; Moriarty, Patrick M; Baum, Seth J; Hurh, Eunju; Bartlett, Victoria J; Kingsbury, Joyce; Figueroa, Amparo L; Alexander, Veronica J; et al. (European heart journal, 2022)
Abstract Aims Hypertriglyceridaemia is associated with increased risk of cardiovascular events. This clinical trial evaluated olezarsen, an N-acetyl-galactosamine-conjugated antisense oligonucleotide targeted to hepatic APOC3 mRNA to inhibit apolipoprotein C-III (apoC-III) production, in lowering triglyceride levels in patients at high risk for or with established cardiovascular disease. Methods and results A randomized, double-blind, placebo-controlled, dose-ranging study was conducted in 114 patients with fasting serum triglycerides 200–500 mg/dL (2.26–5.65 mmol/L). Patients received olezarsen (10 or 50 mg every 4 weeks, 15 mg every 2 weeks, or 10 mg every week) or saline placebo subcutaneously for 6–12 months. The primary endpoint was the percent change in fasting triglyceride levels from baseline to Month 6 of exposure. Baseline median (interquartile range) fasting triglyceride levels were 262 (222–329) mg/dL [2.96 (2.51–3.71) mmol/L]. Treatment with olezarsen resulted in mean percent triglyceride reductions of 23% with 10 mg every 4 weeks, 56% with 15 mg every 2 weeks, 60% with 10 mg every week, and 60% with 50 mg every 4 weeks, compared with increase by 6% for the pooled placebo group (P-values ranged from 0.0042 to <0.0001 compared with placebo). Significant decreases in apoC-III, very low-density lipoprotein cholesterol, non-high-density lipoprotein cholesterol, and apolipoprotein B were also observed. There were no platelet count, liver, or renal function changes in any of the olezarsen groups. The most common adverse event was mild erythema at the injection site. Conclusion Olezarsen significantly reduced apoC-III, triglycerides, and atherogenic lipoproteins in patients with moderate hypertriglyceridaemia and at high risk for or with established cardiovascular disease. Trial registration number NCT03385239. Structured Graphical Abstract Structured Graphical Abstract Potential clinical indications for olezarsen. Triglyceride levels represent a continuum of risk with levels 1.7–5.6 mmol/L (150–500 mg/dL) representing primarily cardiovascular disease risk (cardiovascular disease prevention), levels between 5.6 and 10.0 mmol/L (500–885 mg/dL) representing both cardiovascular disease and pancreatitis risk and >10.0 mmol/L primarily pancreatitis risk in patients with familial chylomicronemia syndrome and multifactorial chylomicronemia syndrome (represented by milky plasma). Treatment with olezarsen with the planned Phase 3 doses of 50 and 80 mg subcutaneously monthly would be expected to substantially reduce triglyceride levels in the entire continuum of hypertriglyceridaemia.